Dampak Pelatihan Cerdas Finansial terhadap Pengembangan Sumber Daya Manusia (SDM) pada Siswa-Siswi SMK Al-Afsar Karangnunggal - Reza Faizal Anshori (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to analyze the impact of smart financial training on human resource (HR) development among students of SMK Al-Afsar Karangnunggal. The research employs a mixed-methods approach combining quantitative and qualitative methods. Quantitative data were collected through pre-test and post-test questionnaires involving 60 respondents, while qualitative data were obtained through in-depth interviews and observations of 30 students. The quantitative analysis used a paired sample t-test, whereas qualitative data were analyzed using thematic analysis. The results indicate a significant improvement in students’ financial literacy, as reflected by an increase in the mean score from 62.4 to 81.7 with a significance value of 0.000 (<0.05). Furthermore, behavioral changes were observed, including improved saving habits, budgeting practices, and controlled spending behavior. Smart financial training contributes to the enhancement of students’ cognitive, affective, and behavioral competencies, as well as their work readiness and economic independence. This study recommends integrating financial literacy into vocational education curricula to strengthen human resource quality.